2011
DOI: 10.1080/08995605.2011.616821
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Relationship Dissolution Among Reserve Soldiers

Abstract: The military has sought to prevent intimate partner violence (IPV) and relationship dissolution. This study examined the longitudinal associations of psychosocial, demographic, and military service characteristics with IPV and relationship dissolution among 546 married or cohabiting reservist military personnel that both mobilized and demobilized during an approximate 8-month period in 2003. Over 13% reported engaging in IPV in the year prior to mobilization. Younger age and more stress were associated with IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The majority ( n = 31) of included studies reported past-year IPV perpetration ( Buchholz et al, 2017 ; Byrne & Riggs, 1996 ; Dutra, de Blank, Scheiderer, & Taft, 2012 ; Fonesca et al, 2006 ; Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock, Szarka, Cox, & Harel, 2016 ; Gondolf & Foster, 1991 ; Heavey, Homish, Goodell, & Homish, 2017 ; Heyman & Neidig, 1999 ; Hiley-Young, Blake, Abueg, Rozynko, & Gusman, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Kelley, Stambaugh, Milletich, Veprinsky, & Snell, 2015 ; Klaw, Demers, & Da Silva, 2016 ; McCarroll et al, 2010 ; Merrill, Crouch, Thomsen, Guimond, & Milner, 2005 ; Newby et al, 2003 ; Owens et al, 2013 ; Pan, Neidig, & O'Leary, 1994 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, Knudson, & Fancher, 2002c ; Schmaling, Blume, & Russell, 2011 ; Sherman, Sautter, Jackson, Lyons, & Han, 2006 ; Slep, Foran, Heyman, & Snarr, 2011 ; Smith Slep, Foran, Heyman, & Snarr, 2010 ; Stander et al, 2011 ; Taft et al, 2009 ; Teten et al, 2010 ; Teten, Schumacher, Bailey, & Kent, 2009 ; Tharp, Sherman, Bowling, & Townsend, 2016 ). The remaining studies measuring IPV in different time periods (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The majority ( n = 31) of included studies reported past-year IPV perpetration ( Buchholz et al, 2017 ; Byrne & Riggs, 1996 ; Dutra, de Blank, Scheiderer, & Taft, 2012 ; Fonesca et al, 2006 ; Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock, Szarka, Cox, & Harel, 2016 ; Gondolf & Foster, 1991 ; Heavey, Homish, Goodell, & Homish, 2017 ; Heyman & Neidig, 1999 ; Hiley-Young, Blake, Abueg, Rozynko, & Gusman, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Kelley, Stambaugh, Milletich, Veprinsky, & Snell, 2015 ; Klaw, Demers, & Da Silva, 2016 ; McCarroll et al, 2010 ; Merrill, Crouch, Thomsen, Guimond, & Milner, 2005 ; Newby et al, 2003 ; Owens et al, 2013 ; Pan, Neidig, & O'Leary, 1994 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, Knudson, & Fancher, 2002c ; Schmaling, Blume, & Russell, 2011 ; Sherman, Sautter, Jackson, Lyons, & Han, 2006 ; Slep, Foran, Heyman, & Snarr, 2011 ; Smith Slep, Foran, Heyman, & Snarr, 2010 ; Stander et al, 2011 ; Taft et al, 2009 ; Teten et al, 2010 ; Teten, Schumacher, Bailey, & Kent, 2009 ; Tharp, Sherman, Bowling, & Townsend, 2016 ). The remaining studies measuring IPV in different time periods (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Much of this aggression and violence is likely to be acted out in the family home. Indeed, US research has established that domestic violence and abuse [with a focus on intimate partner violence (IPV)] is prevalent among military populations (McCarroll et al 2000; Bradley, 2007; Foran et al 2011; Schmaling et al 2011). Research has suggested a strong association between military factors, including combat exposure, and IPV perpetration as well as highlighted the role that mental health problems can play in IPV perpetration among military personnel (Marshall et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in a 2013 IOM report (Institute of Medicine, IOM, 2013), recent increases in the length of deployments and number of redeployments have placed considerable strain on military families (e.g. Andres, 2014;Chandra et al, 2008;Gorman et al, 2011;Mansfield et al, 2010;Riviere et al, 2012;Schmaling et al, 2011). On a national survey of 819 randomly selected OEF/OIF/OND veterans conducted by The Washington Post and Kaiser Family Foundation (2014), 45% of respondents endorsed "sometimes" or "often" having relationship problems with their spouse or partner, and 19% reported relationship problems with their children.…”
Section: Introductionmentioning
confidence: 99%